ANALISIS PENGARUH HARGA DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN PRODUK SARI ROTI DI KOTA SEMARANG - Danny Kurniawan; Apriatni Endang Prihatini (Jurnal Ilmu Administrasi Bisnis, 2018)
Bread is one of the sources of carbohydrates beside rice. Currently, the function of bread is not only eaten for breakfast but also for lunch and dinner because bread is simple food to eat for consumers with multitask activity. Sari Roti product which has variety of bread such as white bread, sweet bread, sandwich, and dorayaki produced by PT. Nippon Indosari,Tbk. This research aims to know the influence of Pice, and Product Quality towards Buying Decision of Product Sari Roti in Semarang. Sample in this research are 100 consumers who have purchased and consume product of Sari Roti. Data analysis that is used are correlation test, simple regression, multiple regression, and classic assumption proceed by SPSS Program. The result of this research shows that price and product quality positive influence towards buying decision partially and simultantly. The conclusion for this research is the better Product of Sari Roti price and product quality are, the higher buying decision that is done by the consumers of Product Sari Roti in Semarang.